2008
DOI: 10.1115/1.2844582
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical and Experimental Study on the Effect of the Cone Angle of the Spindle in Murata Vortex Spinning Machine

Abstract: To study the effect of the cone angle of the hollow spindle in the nozzle of Murata vortex spinning (MVS) on yarn properties, the k‐ε turbulence model is employed to simulate the airflow patterns inside the different nozzles with different spindle cone angles. A set of corresponding spinning experiments is designed to verify numerical predictions. The simulation results show that some factors, such as the counter-rotating vortex pair (CVP) over the spindle, high supersonic zone in the inlet of the swirling cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…With regard to yarn hairiness, it was observed that the yarn samples in counts of 20 Figure 11. Neps of carded yarns.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to yarn hairiness, it was observed that the yarn samples in counts of 20 Figure 11. Neps of carded yarns.…”
Section: 17mentioning
confidence: 99%
“…[4][5][6][7][8] Most of the studies regarding the vortex spinning system investigated the influences of processing parameters on the yarn structure and properties. 7,9,[12][13][14][15][16][17][18][19][20][21][22][23] From these studies, it can be concluded that when 100% cotton and cotton-rich blended yarns are produced, the yarn quality deteriorates considerably. 7,15,16,22,23 The range of the yarn count spinnable on the system is claimed by the machinery makers to be between 15-20 Ne and 50-60 Ne.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al performed numerical simulation using computational fiuid dynamics of the airflow pattem inside the twisting system of vortex spinning to study the effect of spindle cone angle on the yam properties [7]. Based on the simulated results of the airflow pattem, only the possible dynamics of the fiber strand and yam were analyzed, while the direct data on the fiber/air two-phase flow were not obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the characteristics of the flow field distribution, the possible rules of the fiber motion were discussed (Guo, An, Yu, & Yu, 2008;Pei & Yu, 2009). However, these numerical or theoretical researches only obtained the data of the single-phase airflow without the direct data of the fibers in the airflow and the interaction between the fibers and the airflow or the wall.…”
Section: Introductionmentioning
confidence: 99%